The pedagogy approach for enhancing creativity and innovation in the product design process: a case study approach / Shaira Ismail, Nurul Hayani Abd Rahman and Nani Ilyana Shafie - Ismail, Shaira; Abd Rahman, Nurul Hayani; Shafie, Nani Ilyana (Universiti Teknologi MARA, Kedah, 2023)
The case study focused on the pedagogical approach to enhancing creativity and innovation among the science and technology students of the UiTM Pulau Pinang Branch. The sample for this study consisted of 46 degree-seeking students from the Faculty of Mechanical Engineering. The entrepreneurship course - ENT600 requires them to innovate technology-based products and services. The case study collected data in the product design process during the teaching and learning process. The process of generating ideas was based on the product design process. The phases of product and service design were recorded and justified with the achievement of awards gained by participating in the invention and innovation competition. The findings revealed that the intervention strategies contribute to the successful creation and innovation of product and service ideas. The pedagogical approach based on the facilitator's or lecturer’s intervention enhanced students’ innovativeness and creativity. It has been revealed that the intervention phase has activated and motivated students’ product or service idea generation. During the intervention process, students showed high participation in justifying their ideas, increasing creative thinking and problem-based learning. This project-based learning contributes to the innovative and creative teaching method by starting with addressing the problems or issues in the beginning, finding solutions, and entering a new phase of intervening, justifying, approving, and testifying, sketching, and evaluating ideas. The instructional strategies of probing questions for justifications have created a high participation rate in classroom discussions, enhancing creative thinking and problem solving where students are engaged in the learning process to support and justify ideas.